Idea wspólnoty etnolingwistycznej Słowian w prelekcjach paryskich Mickiewicza = The Idea of the Ethnolinguistic Unity of the Slavs in Mickiewicz`s Paris lectures - Krysowski, Olaf (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Adam Mickiewicz created the image of the Slavs` identity in Paris lectures in reference to the process of language development and the dynamics of changes within it. He perceived language not only as a tool for learning about the history and culture of the Slavs but also as a factor that can restore the unity of these seemingly different and dispersed peoples, who have common roots and who form a single community under ethnic and civilizational considerations. By proclaiming such an opinion, professor at Coll?ge de France tried not only to rise above the "political divisions" but also to override sociocultural differences that have grown over the centuries within this once more or less consolidated, community.
Keywords: Mickiewicz, Adam (1798-1855); wspólnota etnolingwistyczna; pochodzenie etniczne; ethnolinguistic unity of the Slavs; ethnicity